2009
DOI: 10.1590/s0100-736x2009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Survey on control and management practices of equine helminthes infection

Abstract: Pesq. Vet. Bras. 29(3):253-257, março 2009 RESUMO.-[Inquérito sobre práticas de manejo e controle das helmintoses em éguas no Brasil.] Vinte nove haras foram selecionados na região do Médio Paraíba, Estado do Rio de Janeiro, os responsáveis pelos animais entrevistados e amostras fecais de éguas foram coletadas e submetidas às técnicas de OPG, Coprocultura, Sedimentocentrifugo-flutuação, Ueno e Baermann modificadas. A prevalência dos helmintos para as éguas e haras foi calculada. A capacidade de suporte, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
3
19
0
4
Order By: Relevance
“…Several studies have shown that pasture management is one of the tools to maximize the control of helminths in the property, thereby reducing the frequency of anthelmintic treatments in animals (Earle et al 2002, O'Meara & Mulcahy 2002. Martins et al (2009) found similar results to those of the present study, showing that 67.9% of creators perform pasture rotation, 89.3% remove faeces from stalls and, on the other hand, no creator removes feces from pickets, probably due to to labor and possible high costs. O ' Meara & Mulcahy (2002) also reported that 71% of creators apply pasture rotation on their property and only 32% withdraw feces from pickets.…”
Section: Resultssupporting
confidence: 90%
“…Several studies have shown that pasture management is one of the tools to maximize the control of helminths in the property, thereby reducing the frequency of anthelmintic treatments in animals (Earle et al 2002, O'Meara & Mulcahy 2002. Martins et al (2009) found similar results to those of the present study, showing that 67.9% of creators perform pasture rotation, 89.3% remove faeces from stalls and, on the other hand, no creator removes feces from pickets, probably due to to labor and possible high costs. O ' Meara & Mulcahy (2002) also reported that 71% of creators apply pasture rotation on their property and only 32% withdraw feces from pickets.…”
Section: Resultssupporting
confidence: 90%
“…These results are consistent with other surveys. In Sweden, mixed grazing was found in 10% of horse farms (Lind et al, 2007), while 39% of horse breeders sampled in Rio de Janeiro state (Brazil) indicated they used mixed grazing with ruminants as an alternative to control strongyles and for better pasture management (Martins et al, 2009). These results strongly contrast with what has been observed in Irish equine farms, where 71% of respondents were aware of the health benefits of mixed grazing and utilized it effectively to lower strongyle pasture contamination (O'Meara and Mulcahy, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In these farms, the proportion of grasslands under both cut and grazed management was also the highest, and early cuts under mixed management are known to strongly decrease the number of infective larvae in pastures (Martin-Rosset, 2015). Nearly 60% of these farms had an annual stocking rate lower than 0.6 LU/ha, which is likely to reduce the risks of strongyle infection by horses (Martins et al, 2009). There was also a high frequency of deworming treatments in these specialized farms, where breeders partly based deworming decisions on indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horses, among most domestic animals are reported to be more susceptible to a large number of parasites and may harbor different species at any time (Wannas, et al, 2012). An apparently healthy horse can harbor over onehalf million Gastrointestinal Intestinal Parasites (GIP) such as protozoa, trematodes, cestodes and nematodes (Martins et al, 2009;Stoltenow and Purdy, 2003). This is because, the gastrointestinal tract provides favorable environment for the survival and proliferation of many of these parasites (Egan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%